2017
DOI: 10.1073/pnas.1716245115
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the leinamycin family of natural products by mining actinobacterial genomes

Abstract: Nature's ability to generate diverse natural products from simple building blocks has inspired combinatorial biosynthesis. The knowledge-based approach to combinatorial biosynthesis has allowed the production of designer analogs by rational metabolic pathway engineering. While successful, structural alterations are limited, with designer analogs often produced in compromised titers. The discovery-based approach to combinatorial biosynthesis complements the knowledge-based approach by exploring the vast combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 47 publications
6
135
0
Order By: Relevance
“…Six HCSs from CB00144, CB00158, CB01229, CB01357, CB01456 and CB01509, are in the same cluster with SnaI (CBW45745.1) and VirC (BAF50725.1) involved in the biosynthesis of streptogramin A‐type antibiotics. Four HCSs from CB01828, CB01882, CB01883 and CB02980 are similar to LnmM, suggesting their involvement in the biosynthesis of the recently identified LNM‐family of natural products, in which a novel polyketide weishanmycin was identified from CB01883 using an alternative probe of DUF‐SH domain (Pan et al ., ). The HCS from CB02999 shares 98% sequence similarity with BaeG, while HCSs from CB00111 and CB01881 form a unique sub‐branch.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Six HCSs from CB00144, CB00158, CB01229, CB01357, CB01456 and CB01509, are in the same cluster with SnaI (CBW45745.1) and VirC (BAF50725.1) involved in the biosynthesis of streptogramin A‐type antibiotics. Four HCSs from CB01828, CB01882, CB01883 and CB02980 are similar to LnmM, suggesting their involvement in the biosynthesis of the recently identified LNM‐family of natural products, in which a novel polyketide weishanmycin was identified from CB01883 using an alternative probe of DUF‐SH domain (Pan et al ., ). The HCS from CB02999 shares 98% sequence similarity with BaeG, while HCSs from CB00111 and CB01881 form a unique sub‐branch.…”
Section: Resultsmentioning
confidence: 97%
“…A recent metagenomic analysis suggested that AT‐less type I PKSs may constitute about 38% of modular PKSs among the sequenced bacterial genomes (O'Brien et al ., ). Our discovery of the LNM family of natural products through in silico and genome mining also revealed that there is huge potential for structure diversity from AT‐less type I PKSs (Pan et al ., ). Although KSs in either type I or II PKSs have been used to survey the structure diversity of PKSs in different geographic locations (Charlop‐Powers et al ., ; Charlop‐Powers et al ., ), the diversity of AT‐less type I PKSs in the environment, to our knowledge, has not been explored in a systematic manner.…”
Section: Introductionmentioning
confidence: 97%
“…3 Each lnm -type gene cluster contains at least one P450. Interestingly, the GNMs and WSMs do not have 1,3-dioxo-1,2-dithiolane rings or hydroxyl groups at C-8 or C-4′ (Figure S5), suggesting alternate or cryptic roles for these P450s.…”
Section: Resultsmentioning
confidence: 99%
“…With the recent discovery of 28 lnm -type gene clusters, 3 it is fascinating to consider the potential biosynthetic and biological implications of LNM-like natural products that are structurally distinct to 1 . For example, the GNMs and WSMs, which do not possess the 1,3-dioxo-1,2-dithiolane rings or hydroxyl groups at C-8 or C-4′, are likely significantly less active than 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation